SCENARIO OF PUBLICATIONS ON THE EPIDEMIOLOGICAL AND CLINICAL PROFILE OF BREAST CANCER: SCOPING REVIEW - Marmitt, Natália; Innocente, Agnes Peruzzo; Vargas, Sheron Tannara; Dahmer, Alessandra; Terres, Mellina da Silva; Taveira, Daniele Giroleti; Sosnoski, Monalisa; Costa, Michele da Rosa; Mazur, Aline de Souza (Seven Editora, 2025)
Breast cancer is still the type of cancer that most affects and kills women worldwide. Due to its heterogeneity in histology, prognosis, and therapeutic options, it remains a current issue and a public health challenge. The objective of this study was to describe and synthesize the clinical and epidemiological profile of women with breast cancer. This is a scoping review, composed of open access articles, in Portuguese and English, published in the last 5 years. The profile was found with a median age of 54.5 years, predominant age group between 50 and 69 years, white skin color, incomplete elementary or high school education, housewives, with moderate economic status, within the ideal weight, married, users of public health services, without comorbidities, with a gynecological history of 1 (one) delivery or more, premenopausal women, not smokers or alcoholics. Regarding the histological profile, invasive ductal carcinoma predominated, disease stages II and III, estrogen and progesterone receptor positive, HER 2 negative, histological grade III, tumor size between 2-5 cm, negative lymph nodes and no presence of metastases. Understanding the clinical and epidemiological profile of women with breast cancer allows for assertive and coordinated public policies for care. DOI: https://doi.org/10.56238/sevened2025.021-018